see the attached file and answer it for me
Attachments:
![](https://hi-static.z-dn.net/files/d05/d8a059b2853ce553b3f5451fa9f1d66a.jpg)
Answers
Answered by
0
MATE
YOUR SOLUTION IS IN ATTACHED PICTURE ☺️
Attachments:
![](https://hi-static.z-dn.net/files/df4/f5ff4eeec691f4346eeedc1c81c974ba.jpg)
Answered by
3
Step-by-step explanation:
Given that, mth term=1/n and nth term=1/m.
then ,let a and d be the first term and the common difference of the A.P.
so a+(m-1)d=1/n...........(1) and a+(n-1)d=1/m...........(2).
subtracting equation (1) by (2) we get,
md-d-nd+d=1/n-1/m
=>d(m-n)=m-n/mn
=>d=1/mn.
again if we put this value in equation (1) or (2) we get, a=1/mn.
then, let A be the mnth term of the AP
a+(mn-1)d=1/mn+1+(-1/mn)=1
hence proved.
Similar questions